Mapping a leaf rust resistance gene LrOft in durum wheat Ofanto and its suppressor SuLrOft in common wheat - Zhuansun, Xiangxi; Sun, Junna; Liu, Nannan; Zhang, Shengnan; Wang, Huifang; Hu, Zhaorong; Ma, Jun; Sun, Qixin; Xie, Chaojie (Frontiers in Plant Science, 2023)
Epidemics of leaf rust (caused by the fungal pathogen Puccinia triticina Erikss., Pt) raise concerns regarding sustainability of wheat production. Deployment of resistant cultivars is the most effective and economic strategy for combating this disease. Ofanto is a durum wheat cultivar that exhibits high resistance to Pt race PHT throughout its entire growing period. In the present study, we identified a leaf rust resistance gene in Ofanto and temporarily designated it as LrOft. LrOft was mapped to a 2.5 cM genetic interval in chromosome arm 6BL between Indel markers 6B6941 and 6B50L24. During introgression of LrOft from Ofanto to common wheat it was observed that F1 plants of Ofanto crossed with Shi4185 exhibited leaf rust resistance whereas the F1 of Ofanto crossed with ND4503 was susceptible. In order to map the presumed suppressor locus, a Shi4185/ND4503//Ofanto three-way pentaploid population was generated and SuLrOft was mapped on chromosome arm 2AS. SuLrOft was mapped within a 2.6 cM genetic interval flanked by 2AS50L14 and 2AS50L6. Fine mapping using 2,268 plants of the three-way cross narrowed the suppressor locus to a 68.2-kbp physical interval according to IWGSC RefSeq v1.1. Sequence analysis of genes in the physical interval revealed that TraesCS2A02G110800 encoding an RPP-13-like protein with an NB-ARC domain was a potential candidate for SuLrOft.